2020
DOI: 10.1002/pon.5390
|View full text |Cite
|
Sign up to set email alerts
|

Being a mother after a cancer diagnosis during pregnancy: Maternal psychosocial functioning and child cognitive development and behavior

Abstract: ObjectiveUp to 51.5% of women diagnosed with cancer during pregnancy experience trauma (eg, intrusive thoughts, avoidance) and 20% report anxiety. Maternal anxiety can negatively affect child behavior among the noncancer population. This study aims to elucidate relationships between maternal distress, parenting style, and child behavior and development among women with cancer during pregnancy.MethodsThis cross‐sectional study of child cognitive, language and motor development analyze child behavior in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Platinum derivatives during pregnancy were indicated as a potential risk factor for decreased cortical gyrification of the left superior temporal gyrus. However, chemotherapy during pregnancy in general did not significantly contribute to these findings, resonating with earlier findings [ 14 , 19 ] describing the role of the psychosocial impact of cancer during pregnancy on the neurocognitive functioning of the child. Balancing between pros and cons on the use of chemotherapy during pregnancy, the current data favour the use of chemotherapy during pregnancy when clinically indicated.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Platinum derivatives during pregnancy were indicated as a potential risk factor for decreased cortical gyrification of the left superior temporal gyrus. However, chemotherapy during pregnancy in general did not significantly contribute to these findings, resonating with earlier findings [ 14 , 19 ] describing the role of the psychosocial impact of cancer during pregnancy on the neurocognitive functioning of the child. Balancing between pros and cons on the use of chemotherapy during pregnancy, the current data favour the use of chemotherapy during pregnancy when clinically indicated.…”
Section: Discussionsupporting
confidence: 87%
“…The psychosocial impact of a cancer diagnosis during pregnancy might partially explain these findings. A recent study identified maternal death as a potential risk factor in their findings of decreased verbal intelligence in children born after cancer-complicated pregnancies [14] and another study described a relationship between infant behavioural functioning and maternal psychological wellbeing [19] . However, given that only 12/42 mothers in the study group did not receive chemotherapy during pregnancy and the heterogeneity of chemotherapy regimens used, we cannot exclude that some chemotherapeutics might directly or indirectly affect neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The death of the mother is a major life event that potentially influences child development. Previous studies have shown an association between anxiety and stress during pregnancy with adverse birth outcomes (e.g., spontaneous abortion, preterm labor, growth restriction) and problems across several domains (cognitive, behavioral and emotional) in the child (Betchen et al, 2020;Van den Bergh et al, 2005). In subgroup analyses, receiving supportive care was associated with the death of the mother.…”
Section: Discussionmentioning
confidence: 85%
“…However, various abnormalities were observed in child behavior and executive function after prenatal exposure to chemotherapy during the second and third trimester; weak emotional regulation, and high rates of internalizing, externalizing, and total behavior problems were observed. These findings may also be attributed to antenatal maternal stress, as several studies have demonstrated that maternal psychosocial functioning during pregnancy is highly associated with child cognition [37][38][39]. Thus, it is possible that child behavior and executive function are both influenced by the stress caused by cancer diagnosis during pregnancy.…”
Section: Discussionmentioning
confidence: 98%